先化简,在求值:(x-y)²+(3x-2y)(2x+y)-x(6x-y)
3个回答
原式
=x²-2xy+y²+6x²+3xy-4xy-6x²+xy
=x²-2xy+y²
=(x+y)²
当x=2分之1,y=1时,
原式
=(2分之1+1)²
=(2分之3)²
=4分之9
相关问题
先化简,再求值:(x-y)(x+y)-(x+y)^2+2y(y-x),其中x=1,y=3.
先化简,在求值 3x+5(6x*5y)-5x+6y 其中x=2 y=5
先化简再求值,(2x-3y)^2-(x-2y)(x-5y)-(2x+y)(2x-y)
先化简在求值:(2X-Y)(Y+2X)-(2y+X)(-2y-x),其中x=1,y=2
(1)先化简,再求值:2(x-y)2-(y-x)2-(x+y)(y-x),其中x=3,y=-2.
先化简,后求值:x-y/x+3y - x^2-9y^2/x^2+6xy+9y^2 + 2y/x+3y,其中x=2,y=-
化简、求值(1)化简:3(x-2y)+2(3x+y)(2)先化简再求值(3x²y-2xy²)-(xy
先化简,再求值:(2x+6y)2-4x(x+2y)+(-9y)•4y,其中x=-[1/3],y=6.
先化简,再求值:x2−y2x+y-2(x+y),其中x=3,y=-[1/3].
先化简再求值y(x+y)+(x-y)²-x²-2y²其中x=-1/3y=3